Interplay between age‐based competitive asymmetries within the brood and direct competition between inbred and outbred offspring in a burying beetle. (28th November 2018) - Miller, Mhairi; Ratz, Tom; Richardson, Jon; Smiseth, Per T.
Abstract: Theory suggests that intraspecific competition associated with direct competition between inbred and outbred individuals should be an important determinant of the severity of inbreeding depression. The reason is that, if outbred individuals are stronger competitors than inbred ones, direct competition should have a disproportionate effect on the fitness of inbred individuals. However, an individual's competitive ability is not only determined by its inbreeding status but also by competitive asymmetries that are independent of an individual's inbreeding status. When this is the case, such competitive asymmetries may shape the outcome of direct competition between inbred and outbred individuals. Here, we investigate the interface between age‐based competitive asymmetries within broods and direct competition between inbred and outbred offspring in the burying beetle Nicrophorus vespilloides . We found that inbred offspring had lower survival than outbred ones confirming that there was inbreeding depression. Furthermore, seniors (older larvae) grew to a larger size and had higher survival than juniors (younger larvae), confirming that there were age‐based competitive asymmetries. Nevertheless, there was no evidence that direct competition between inbred and outbred larvae exacerbated inbreeding depression, no evidence that inbreeding depression was more severe in juniors and no evidence that inbred juniors suffered disproportionately due to competition from outbred seniors. Our results suggest that direct competition between inbred and outbred individuals does not necessarily exacerbate inbreeding depression and that inbred individuals are not always more sensitive to poor and stressful conditions than outbred ones.